THE SUBJECT OF RECONSTRUCTION REFLECTION - Чуйко, В. Л. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
It is regarded the process of reflection of Ukrainian philosophy.